Clinical efficacy of crizotinib in Chinese patients with ALK-positive non-small-cell lung cancer with brain metastases - Lei, Yuan-Yuan; Yang, Jin-Ji; Zhong, Wen-Zhao; Chen, Hua-Jun; Yan, Hong-Hong; Han, Jie-Fei; Yang, Lu-Lu; Wu, Yi-Long (Journal of Thoracic Disease, 2015)
Background: Crizotinib has been associated with intracranial disease control in anaplastic lymphoma kinase (ALK)-positive non-small-cell lung cancer (NSCLC) patients with brain metastases. Continued crizotinib treatment has also been used for prolonged disease control in patients experiencing isolated central nervous system (CNS) failure. However, there are few studies of crizotinib efficacy in ALK-positive Chinese patients. Thus, we retrospectively investigated the clinical efficacy of crizotinib in Chinese ALK-positive NSCLC patients with brain metastases at baseline, and evaluated the clinical benefit of continuing crizotinib beyond CNS failure. Methods: A total of 120 advanced ALK-positive NSCLC patients treated with crizotinib were enrolled with 38 having brain metastases at baseline. The objective response rate (ORR) and progression-free survival (PFS) were compared between patients with and without brain metastases at baseline. A subset of patients who developed CNS failure continued crizotinib treatment beyond progressive disease (PD), and the second PFS from the time of the first progression was also evaluated. Results: The ORR of crizotinib was similar between patients with and without brain metastases at baseline (68.4% vs. 69.5%, P=0.904). However, the patients without brain metastases at baseline experienced a longer median PFS [10.0 months, 95% confidence interval (CI), 7.6-12.5 vs. 7.0 months, 95% CI, 6.4-7.6; P=0.021]. Among 88 patients with PD defined Response Evaluation Criteria in Solid Tumors (RECIST), 33 developed CNS failure. A total of 24 patients who developed CNS failure continued crizotinib treatment beyond PD, and they achieved a second median PFS of 6.3 months (95% CI, 2.9-9.7). Conclusions: Chinese ALK-positive NSCLC patients with brain metastases achieved a similar response to crizotinib and significantly shorter PFS compared to those without brain metastases at baseline. Continuous administration of crizotinib beyond PD in patients developing CNS failure appeared to be a valid treatment strategy.